2019
DOI: 10.3390/polym11111778
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Performance of 3D Printed Wood-PLA/PHA Using Fused Deposition Modelling: Effect of Printing Temperature

Abstract: The microstructure and mechanical performance of wood-based filament is investigated in the case of Fused Deposition Modelling (FDM) technique using experimental and numerical approaches. The printing process of wood-PLA/PHA is conducted by varying the printing temperature, typically from 210 °C to 250 °C. The filament temperature during the laying down is measured using infra-red camera to study the thermal cycling. In addition, X-ray micro-tomography is used to evaluate the material arrangement of printed wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 34 publications
3
59
2
Order By: Relevance
“…Engineering stress levels as large as 250 MPa are obtained with a significant elongation at break between 151% and 169%. The elongation at break capability of nylon filament contrasts with former results obtained for PLA reinforced by wood particles 27 or hemp fibers, 28 where a limited stretching of less than 10% is observed. This limitation can be attributed to the interfacial role within the filament itself.…”
Section: Mechanical Behaviorcontrasting
confidence: 93%
See 1 more Smart Citation
“…Engineering stress levels as large as 250 MPa are obtained with a significant elongation at break between 151% and 169%. The elongation at break capability of nylon filament contrasts with former results obtained for PLA reinforced by wood particles 27 or hemp fibers, 28 where a limited stretching of less than 10% is observed. This limitation can be attributed to the interfacial role within the filament itself.…”
Section: Mechanical Behaviorcontrasting
confidence: 93%
“…This means also that computations performed on the full specimen become reliable when this sample is imaged with resolutions larger than 3.6 million voxels. Based on former results published by the authors, a better stability of the predicted stiffness is obtained for materials such as wood-PLA/PHA, 27 ASA or PETG 29,30 even for voxel sizes as large as 143 μm. This larger stability of the predictions is found mainly correlated to the sensitivity of the porosity content to the change of resolution.…”
Section: Finite Element Predictionsmentioning
confidence: 78%
“…Lastly, a printing test was successfully performed with a larger printer to assess the viability of producing large-scale structures. PLA+PHA with pinewood fiber was used by Guessasamo et al [ 72 ], and the result revealed a tendency for heat accumulation at high printing temperatures. However, there was very limited improvement in the tensile performance at these temperatures, making 220 °C an ideal choice for printing the wood-based filament.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Guessasma et al [ 72 ] noticed that higher temperatures above 230 °C were not advisable, as thermal degradation of wood particles occurred between 210 °C and 370 °C, and higher temperatures affected the tensile properties. It was concluded that the elongation of printed objects at the breaking point was fully restored and a loss of mechanical performance was seen by 41% and 35% stiffness and strength, respectively, using the best printing conditions.…”
Section: Printing Failures and Issuesmentioning
confidence: 99%
See 1 more Smart Citation